Sales Transactions Of Reman Business At Pt United Tractors Tbk - Pambayun, Bagas Arya; Roostika, Raden Roro Ratna (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
PT United Tractors Tbk, a subsidiary of PT Astra International, is Indonesia’s largest distributor of construction machinery and heavy equipment, serving as the sole distributor for brands such as Komatsu, UD Trucks, Scania, Bomag, and Tadano. This internship provided valuable exposure to the transaction system of heavy equipment component sales, covering the process from order initiation to completion, commonly referred to as “done billing.”All transactions at PT United Tractors are managed online through the SAP application, which enables real-time monitoring of order data and minimizes the risk of fraud. During this independent internship, the researcher gained practical knowledge of component sales systems, product promotion to potential customers, maintenance planning, and operational target setting for heavy equipment units.The internship was carried out in the Service Division, specifically the PSBD OBD Department, which manages Reman transactions, including sales of components such as engines, transmissions, axles, cylinders, pumps & motors, and Komatsu Certified Machine Rebuild (KCMR). This experience provided first-hand understanding of the Reman sales transaction system, offering essential insights and skills that will support future career development in the heavy equipment industry.